Enhanced recovery after surgery pathway for patients undergoing cardiac surgery: a randomized clinical trial. (5th March 2018) - Li, Man; Zhang, Junjie; Gan, Tong J; Qin, Gang; Wang, Lu; Zhu, Maoen; Zhang, Zhong; Pan, Yundan; Ye, Zhi; Zhang, Fan; Chen, Xuliang; Lin, Guoqiang; et al.
Abstract: OBJECTIVES: Enhanced recovery after surgery (ERAS) pathways have not been reported in cardiac surgery. The aim of this study was to evaluate the clinical effectiveness and safety profile of ERAS pathways compared with routine care for patients undergoing cardiac valvular surgery. METHODS: A randomized clinical trial was conducted between July 2015 and November 2016. A total of 226 patients who underwent elective valvular surgery were randomly assigned to the ERAS pathway or routine care (control) group. The ERAS protocol consisted of an evidence-based systematic optimization approach for managing perioperative patients. The control group received routine care. The primary end-point was readiness for hospital discharge. The secondary outcomes were duration of intensive care unit (ICU) stay, length of postoperative vasoactive drug support, duration of mechanical ventilation, time to first bowel movement, removal of surgical drain, overall medical costs and complication rate. RESULTS: Postoperative time to readiness for discharge was significantly shorter in the ERAS group (6.0 (2.0∼14.0) days) than the control group (7.0 (4.0∼16.0) days, P  =   0.01), and the duration of ICU stay and duration of mechanical ventilation were significantly shorter in the ERAS group (20.9 (13.5∼69.3) h, 7.2 (0.0∼22.3) h, respectively) than the control group (22.0 (13.4∼212.3) h, P  =   0.001; 8.8 (3.7∼44.9) h, respectively; P  < 0.0001). The overall treatment cost of the ERAS group (69202 (52089∼123823) CNY) was significantly lower than that of the control group (77058 (51390∼144290) CNY, P  =   0.002). CONCLUSIONS: ERAS pathways reduce the length of ICU and hospital stay, postoperative complications and cost for patients undergoing cardiac surgery. Clinical trial registration: ClinicalTrials.gov: NCT02479581.